2010
DOI: 10.1088/0953-8984/22/44/446001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent spin momentum densities in Ni–Mn–In alloys

Abstract: The spin-dependent electron momentum densities in Ni(2)MnIn and Ni(2)Mn(1.4)In(0.6) shape memory alloy using magnetic Compton scattering with 182.2 keV circularly polarized synchrotron radiation are reported. The magnetic Compton profiles were measured at different temperatures ranging between 10 and 300 K. The profiles have been analyzed mainly in terms of Mn 3d electrons to determine their role in the formation of the total spin moment. We have also computed the spin polarized energy bands, partial and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
5
6
0
Order By: Relevance
“…The reported values have been corrected, especially in the case of Mn, for jj mixing arising due to smaller spin–orbit splitting in the 2p core hole. The total magnetic moment estimated from the present analysis is in good agreement with earlier magnetization measurements . For Ni2Mn1.4In0.6, the Mn and Ni magnetic moments estimated from XMCD are 1.1 and 0.04μB/atom, respectively, giving a total moment of 1.48μB, which agrees well with magnetization value of 1.6μB .…”
Section: Magnetism Of the Martensitic Statesupporting
confidence: 90%
“…The reported values have been corrected, especially in the case of Mn, for jj mixing arising due to smaller spin–orbit splitting in the 2p core hole. The total magnetic moment estimated from the present analysis is in good agreement with earlier magnetization measurements . For Ni2Mn1.4In0.6, the Mn and Ni magnetic moments estimated from XMCD are 1.1 and 0.04μB/atom, respectively, giving a total moment of 1.48μB, which agrees well with magnetization value of 1.6μB .…”
Section: Magnetism Of the Martensitic Statesupporting
confidence: 90%
“…In the IPES spectrum, the broad peak at ~2 eV can be related to the Mn 3d dominated peak at 1 eV. The position of the unoccupied peak varies between 1-2 eV in different DFT calculations [11]. In conclusion, the present experimental data show that the electronic structure of polycrystalline Ni 2 MnSn surface is in good agreement with the bulk band structure calculation, indicating marginal surface effect on the electronic structure.…”
Section: Resultssupporting
confidence: 77%
“…3 and 4) because at this photon energy the valence band is dominated by Ni and Mn 3d states. The calculated spectra show that the main peak is dominated by the Mn 3d minority states [7], whereas the near Fermi edge has similar contributions from Ni 3d and Mn 3d states. Interestingly, the peak position observed in the calculated spectra of Ni 2 MnIn (shown by an arrow in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…[1,2,3,4,5,6] This has prompted many groups to study the electronic structure of these materials. Ahuja et al [7] studied the band structure of Ni 2 MnIn using the full potential linearized augmented plane wave (FPLAPW) method. They found that in the case of majority-spin states, the 3d bands of Ni and Mn atoms overlap with each other and are mostly occupied; whereas for the minority-spin states, the main contribution arises from the Ni 3d states, while the Mn 3d states have hardly any contribution.…”
Section: Introductionmentioning
confidence: 99%